2023
DOI: 10.3390/molecules28020749
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multifunctional Eu(III) Complex Doped Fe3O4/Au Nanocomposite for Dual Photo-Magnetic Hyperthermia and Fluorescence Bioimaging

Abstract: In this paper, the luminescent complex Eu(3-thenoyltrifluoroacetonate)3 was integrated with Fe3O4 and gold (Au) nanoparticles to form a multifunctional nanocomposite, Fe3O4/Au/Eu(TTA)3 (FOASET NC), for dual magnetic-photothermal therapy and biomedical imaging. Upon functionalization with amine-NH2, the FOASET NC exhibits a small size of 60–70 nm and strong, sharp emission at λmax = 614 nm, enhanced by surface plasmon resonance (SPR) of Au nanoparticles that provided an effective label for HT29 colorectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Photothermal experiments were conducted using a laser irradiation (LD808E3WG13, Lasermate group, Inc., Walnut, CA, USA) at a wavelength of 808 nm with a varying power density (from 0.165 to 1.5 W/cm 2 ). For each experiment, a volume of 200 µL of the freshly prepared aqueous colloids of free IONPs and AuNPs, on one hand, and of their TYMV-based hybrids, on the other hand, was considered [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Photothermal experiments were conducted using a laser irradiation (LD808E3WG13, Lasermate group, Inc., Walnut, CA, USA) at a wavelength of 808 nm with a varying power density (from 0.165 to 1.5 W/cm 2 ). For each experiment, a volume of 200 µL of the freshly prepared aqueous colloids of free IONPs and AuNPs, on one hand, and of their TYMV-based hybrids, on the other hand, was considered [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that magnetic hyperthermia is a novel procedure that offers a safe, powerful, and simple treatment method to meet these complicated challenges [92][93][94][95][96]. In this procedure, which has recently seen rapid development, magnetic nanomaterials can be used to improve hyperthermia efficiency compared to traditional hyperthermia methods for the erosion of tumors [97][98][99][100][101][102][103][104][105][106]. The most significant aspect of magnetic hyperthermia is that magnetic nanomaterials are distributed over very small areas so that the temperature behavior of healthy cells is not affected [107][108][109].…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%
“…Moreover, the photothermal therapy has long been limited to superficial tumors; in the best scenario, near-infrared light in the second region can penetrate breast tissue for 10 cm and skull/brain tissue or deep muscle for 4 cm. However, due to tissue absorption and light scattering, the photothermal effect is markedly weakened for the case of deep tumors. Therefore, there have been initiatives to search for more effective hyperthermia therapy approach by consolidating different modulates. An effective strategy involves the synergistic combination of magnetic hyperthermia (MHT) and photothermal therapy (PTT) to generate cumulative heating at a specific site of interest. In addition to the cumulative effect, this combined approach leverages the complementarity of PTT and MHT, leading to a synergistic hyperthermia effect.…”
Section: Introductionmentioning
confidence: 99%